Positive electrode active material, positive plate and lithium ion secondary battery

By adopting specific Li1+qNixCoyMnzO2 positive electrode active materials, the problems of low tap density and poor processing performance of existing lithium-rich materials are solved, and the energy density and circulation performance of lithium-ion secondary batteries are improved.

CN119601647APending Publication Date: 2025-03-11ZHUHAI GUANQI NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411634747.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing lithium-rich materials have low tap density and poor processing performance, which limits the energy density and cycling performance of lithium-ion secondary batteries.

Method used

Li1+qNixCoyMnzO2 is used as the positive electrode active material, with a primary particle size of 55-150 nm, a secondary particle size distribution is concentrated and uniform, and a spherical degree is 0.45-0.90. The positive electrode active material is prepared by mixing a specific precursor with a lithium source and sintering it.

Benefits of technology

The tap density and processing performance of the positive electrode active material are improved, and the energy density and circulation performance of the lithium-ion secondary battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601647A_ABST
    Figure CN119601647A_ABST
Patent Text Reader

Abstract

The invention relates to the field of battery materials, in particular to a positive electrode active material, a positive plate and a lithium ion secondary battery, the chemical formula of the positive electrode active material is Li1 + qNixCoyMnzO2, q is more than 0 and less than or equal to 1, x is more than or equal to 0.2 and less than or equal to 0.45, y is more than or equal to 0.02 and less than or equal to 0.20, and z is more than or equal to 0.35 and less than or equal to 0.78; the primary particle size of the positive electrode active material is 55-150 nm, Dv50 is 3-5 [mu] m, Dv10 is 1-2 [mu] m, Dv90 is 7-9 [mu] m, and (Dv90-Dv10) / Dv50 is 1.3-1.8, and the positive electrode active material under the particle size and particle size distribution is not only concentrated and uniform in particle size distribution, but also can obtain larger compaction density and better sphericity, so that the positive electrode active material has higher compaction density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery materials, and in particular to a positive electrode active material, a positive electrode sheet and a lithium ion secondary battery. Background Art

[0002] With the increasing depletion of fossil energy and the increasingly serious environmental problems, it is necessary to find other lithium-ion secondary batteries that are efficient, environmentally friendly and have the characteristics of repeated charge and discharge. The development of lithium-ion secondary batteries has a history of more than 20 years, and its applications involve many fields such as communications, transportation, military, medical care, and entertainment. In recent years, with the rapid development of electric vehicles, high-energy-density and high-power lithium-ion batteries have become the inevitable direction of the development of lithium-ion batteries in the future. At present, the commercial positive active materials mainly include LiCoO2, LiFePO4, LiMn2O4, and ternary materials, and their specific capacities are all less than 200mAh / g. The positive active material is the main factor limiting the specific energy of the battery. Therefore, in order to develop high-energy-density batteries, it is urgent to find positive active materials with higher specific capacity.

[0003] In recent years, lithium-rich materials with high capacity, low cost, and low toxicity have become a research hotspot and are expected to be used as positive electrode active materials in the next generation of high-energy lithium-ion batteries. However, lithium-rich materials synthesized by existing technologies have low tap density and poor processing performance. Summary of the invention

[0004] The present application provides a positive electrode active material, a positive electrode sheet and a lithium ion secondary battery, which aim to solve the problems of low tap density and poor processing performance of existing lithium-rich materials to a certain extent.

[0005] In a first aspect, the present application provides a positive electrode active material, the chemical formula of the positive electrode active material is as follows: Li 1+q Ni x Co y Mn z O2, and 0<q≤1, 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material is 55-150nm, the secondary particle size Dv50 is 3μm-5μm, Dv10 is 1μm-2μm, Dv90 is 7μm-9μm, (Dv90-Dv10) / Dv50 is 1.3-1.8, and the sphericity is 0.45-0.90.

[0006] In an optional embodiment, the sphericity of the positive electrode active material is 0.6-0.90.

[0007] In an optional embodiment, the specific surface area BET of the positive electrode active material is 1.0-4.0 m 2 / g.

[0008] In an optional embodiment, the specific surface area BET of the positive electrode active material is 1.5-2.5 m 2 / g.

[0009] In an optional embodiment, the porosity of the positive electrode active material is 1-15%.

[0010] In an optional embodiment, the porosity of the positive electrode active material is 3-8%.

[0011] In an optional embodiment, the sulfate content in the positive electrode active material is 66-200 ppm.

[0012] In an optional embodiment, the sulfate content in the positive electrode active material is 66-90 ppm.

[0013] In an optional embodiment, the positive electrode active material satisfies one or two of the following AB:

[0014] A. Powder X-ray diffraction expressed in 2θ angles, with a superlattice peak at 20-25°; optionally, the peak intensity of the superlattice peak at 2θ of 20-25° is 500-1000;

[0015] B. The XRD spectrum of the positive electrode active material satisfies the following relationship: 1.1≤I1 / I2≤1.5; wherein I1 is the peak intensity of the first diffraction peak at 2θ=17-19° in the XRD spectrum; I2 is the peak intensity of the second diffraction peak at 2θ=43-46° in the XRD spectrum.

[0016] In a second aspect, the present application provides a positive electrode active material precursor, the chemical formula of the positive electrode active material precursor is as follows: Ni x Co y Mn z (OH)2, and 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material precursor is 20-200nm, the secondary particle size is 3μm-5μm, and the sphericity is 0.4-0.85.

[0017] In an optional embodiment, the sphericity of the positive electrode active material precursor is 0.6-0.85.

[0018] In an optional embodiment, the sulfate content of the positive electrode active material precursor is 60-180 ppm, preferably 60-80 ppm.

[0019] In an optional embodiment, the porosity of the positive electrode active material precursor is 15-30%.

[0020] In an optional embodiment, the porosity of the positive electrode active material precursor is 19-23%.

[0021] In a third aspect, the present application provides a method for preparing a positive electrode active material, which is prepared by mixing the positive electrode active material precursor with a lithium source and then sintering the mixture.

[0022] In a fourth aspect, the present application provides a positive electrode sheet, which is made from any of the positive electrode active materials described above or the positive electrode active material prepared by the preparation method described above.

[0023] In an optional embodiment, the compaction density of the positive electrode sheet is 2.8 g / cm 3 ~3.20g / cm 3 .

[0024] In a fifth aspect, the present application provides a lithium-ion secondary battery, comprising the positive electrode sheet described in the fourth aspect of the present application, and also comprising a separator, a negative electrode sheet and an electrolyte.

[0025] The technical solution of this application has the following advantages:

[0026] The positive electrode active material provided in the present application has the following chemical formula: Li 1+q Ni x Co y Mn z O2, and 0<q≤1, 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material is 55-150nm, the secondary particle size Dv50 is 3μm-5μm, Dv10 is 1μm-2μm, Dv90 is 7μm-9μm, (Dv90-Dv10) / Dv50 is 1.3-1.8, and the sphericity is 0.45-0.90. The positive electrode active material under this particle size, particle size distribution and sphericity not only has a concentrated and uniform particle size distribution, but also can obtain a larger compaction density, and thus has a higher tap density and better processing performance, thereby improving the energy density and cycle performance of the battery.

[0027] Additional aspects and advantages of the embodiments of the present application will be described and shown in part in the subsequent description, or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0029] Figure 1 It is the first cycle charge and discharge curve of the battery of Example 1 and Comparative Example 1 in the voltage system of 2-4.6V;

[0030] Figure 2 It is the first cycle charge and discharge curve of the battery of Example 1 and Comparative Example 1 in the voltage system of 2-4.8V;

[0031] Figure 3 This is the slice scanning result of the positive electrode active material precursor prepared in Comparative Example 1;

[0032] Figure 4 This is the slice scanning result of the positive electrode active material precursor prepared in Example 1;

[0033] Figure 5 These are the slice XRD results of Example 1 and Comparative Example 1; the ordinate Intensity is translated as intensity. DETAILED DESCRIPTION

[0034] The following examples are provided for a better understanding of the present application, but are not limited to the best implementation mode described, and do not limit the content and protection scope of the present application. Any product identical or similar to the present application obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts shall fall within the protection scope of the present application.

[0035] In the description of the present application, it should be noted that the terms "inside", "outside", etc., indicating the orientation or positional relationship, are based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present application. In addition, the terms "first", "second", and "third" are used for descriptive purposes only, and cannot be understood as indicating or implying relative importance.

[0036] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0037] In addition, the technical features involved in the different embodiments of the present application described below can be combined with each other as long as they do not conflict with each other.

[0038] The present application provides a positive electrode active material, a positive electrode sheet and a lithium ion secondary battery, which can improve the problems of low tap density and poor processing performance of lithium-rich materials synthesized in the prior art. The technical solution adopted in the present application is as follows.

[0039] In a first aspect, the present application provides a positive electrode active material, the chemical formula of the positive electrode active material is as follows: Li 1+q Ni x Co y Mn z O2, and 0<q≤1, 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material is 55-150nm, the secondary particle size Dv50 is 3μm-5μm, Dv10 is 1μm-2μm, Dv90 is 7μm-9μm, (Dv90-Dv10) / Dv50 is 1.3-1.8, and the sphericity is 0.45-0.90. The positive electrode active material under this particle size, particle size distribution and sphericity not only has a concentrated and uniform particle size distribution, but also can obtain a larger compaction density, so it has a higher tap density and better processing performance, thereby improving the energy density and cycle performance of the battery. For example, q is 0.1, 0.5, 1 or in the range of any two of the above values, x is 0.2, 0.3, 0.45 or in the range of any two of the above values, y is 0.02, 0.1, 0.20 or in the range of any two of the above values, z is 0.35, 0.5, 0.78 or in the range of any two of the above values; the primary particle size of the positive electrode active material is 55nm, 100nm, 150nm or above In the range formed by any two values, Dv50 is 3μm, 4μm, 5μm or within the range formed by any two values ​​above, Dv10 is 1μm, 1.5μm, 2μm or within the range formed by any two values ​​above, Dv90 is 7μm, 8μm, 9μm or within the range formed by any two values ​​above, (Dv90-Dv10) / Dv50 is 1.3, 1.5, 1.8 or within the range formed by any two values ​​above. The sphericity is 0.45, 0.6, 0.7, 0.8, 0.85, 0.90 or within the range formed by any two values ​​above.

[0040] The primary particle size of the positive electrode active material and the positive electrode active material precursor refers to the particle size of a single particle in the corresponding material, which is measured by SEM. The secondary particle sizes Dv10, Dv50, and Dv90 refer to the particle sizes after the primary particle size particles are agglomerated, and represent the particle sizes corresponding to the cumulative volume distribution percentages of the corresponding materials reaching 10%, 50%, and 90%, respectively; measured by a laser particle size analyzer.

[0041] The sphericity of the positive electrode active material and the positive electrode active material precursor is calculated by photographing the material by SEM and using imageJ software. The sphericity value (Q, 0<Q<1) is obtained by calculating the ratio of the circumference equivalent diameter and the area equivalent diameter.

[0042] In an optional embodiment, the BET (specific surface area) of the positive electrode active material is 1.0-4.0 m 2 / g. Lithium-rich materials with a BET within this range can have a higher compaction density without affecting the electrochemical performance. For example, the BET of the positive electrode active material is 1.0m 2 / g, 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g or within the range formed by any two of the above values. The specific surface area of ​​the positive electrode active material of the present application is measured by a conventional gas adsorption method.

[0043] In an optional embodiment, the porosity of the positive electrode active material is 1-15%, preferably 3-8%. If the porosity of the positive electrode active material is too large, the cycle performance of the battery will be affected, and if it is too small, the gram capacity of the battery will be affected. By controlling the porosity of the positive electrode active material within the above range, especially within the preferred range, the cycle performance of the battery can be improved while ensuring a higher gram capacity. For example, the porosity of the positive electrode active material is 3%, 5%, 8% or within the range of any two of the above values.

[0044] In an optional embodiment, the sulfate content in the positive electrode active material is 66-200ppm. For example, the sulfate content of the positive electrode active material precursor is 66ppm, 70ppm, 100ppm, 120ppm, 160ppm, 180ppm, 200ppm or within the range of any two of the above values. In an optional embodiment, the sulfate content in the positive electrode active material is 66-90ppm. The sulfate content of the positive electrode active material precursor is 66ppm, 70ppm, 80ppm, 85ppm, 90ppm or within the range of any two of the above values. By regulating the sulfate content of the positive electrode active material within the above range, the cycle performance of the battery can be improved to a certain extent. The sulfate content in the positive electrode active material of this application is obtained by weight method test, and the specific operation steps are carried out in accordance with GB / T 13025.8-91 Salt Industry General Experimental Method for Determination of Sulfate Ions.

[0045] In an optional embodiment, the powder X-ray diffraction of the positive electrode active material expressed in 2θ angle has a superlattice peak at 20-25°; optionally, the peak intensity of the superlattice peak at 2θ of 20-25° is 500-1000. This peak can better reflect the performance of the lithium-rich material. It is generally believed that the performance is optimal when the peak shape is relatively smooth. If the peak shape is sharp and obvious, the performance of the material will have certain defects.

[0046] In an optional embodiment, the XRD spectrum of the positive electrode active material satisfies the following relationship: 1.1≤I1 / I2≤1.5; wherein I1 is the peak intensity of the first diffraction peak at 2θ=17-19° in the XRD spectrum; I2 is the peak intensity of the second diffraction peak at 2θ=43-46° in the XRD spectrum. The applicant has found that when the ratio of I1 to I2 is within the above range, the cycle stability of the positive electrode active material can be improved. This is because the appropriate proportion of Li / Ni mixed arrangement can effectively prevent the migration of transition metals to the Li layer in a high delithiation state, and the Ni in the lithium layer is slightly passivated. 2+ , effectively increasing the Li interlayer spacing, avoiding the shrinkage of the Li layer under high lithium removal state, and effectively improving the rate performance and long cycle stability of the positive electrode active material. For example, the ratio of I1 to I2 can be 1.1, 1.2, 1.3, 1.4, 1.5 or within the range of any two of the above values.

[0047] In a second aspect, the present application provides a positive electrode active material precursor, the chemical formula of the positive electrode active material precursor is as follows: Ni x Co y Mn z(OH)2, and 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material precursor is 20-200nm, the secondary particle size is 3μm-5μm, and the sphericity is 0.4-0.85. The positive electrode active material precursor under this particle size, particle size distribution and sphericity can not only obtain a positive electrode active material with a concentrated and uniform particle size distribution and a large compaction density, but also makes the positive electrode active material have a higher tap density and better processing performance, thereby improving the energy density and cycle performance of the battery. For example, x is 0.2, 0.3, 0.45 or within the range formed by any two of the above values, y is 0.02, 0.1, 0.20 or within the range formed by any two of the above values, z is 0.35, 0.5, 0.78 or within the range formed by any two of the above values; the primary particle size of the positive electrode active material precursor is 20nm, 100nm, 200nm or within the range formed by any two of the above values, the secondary particle size is 3μm, 4μm, 5μm or within the range formed by any two of the above values, and the sphericity is 0.4, 0.6, 0.7, 0.8, 0.85 or within the range formed by any two of the above values.

[0048] In an optional embodiment, the sulfate content of the positive electrode active material precursor is 60-180 ppm. The applicant has found that the sphericity and specific surface area of ​​the precursor are correlated to the sulfate content. When the sulfate content is between 60-180 ppm, the sphericity gradually decreases from 0.85 to 0.7, and the specific surface area gradually increases from 1.5 to 2.5 m 2 / g, this is because under the influence of charge and hydrogen bond forces, sulfate will exist on the surface or inside of the precursor particles by surface adsorption, inclusion, oxidation or other high-valent metal ion doping. Due to the adsorption of sulfate ions to ions in the overall precursor particles, the particle morphology will be more uneven, and the particles with high sulfate content will have a larger specific surface area and a looser structure. The precipitation will undergo uneven adsorption growth, resulting in a decrease in the sphericity of the particles. The present application can improve the sphericity of the positive electrode active material precursor and reduce the specific surface area without affecting the electrochemical performance by controlling the sulfate content at 60-180ppm, thereby improving the tap density of the positive electrode active material, better cycle DCR data and a smaller K value. For example, the sulfate content of the positive electrode active material precursor is 60ppm, 70ppm, 100ppm, 120ppm, 160ppm, 180ppm or within the range of any two of the above values.

[0049] The sulfate content in the positive electrode active material precursor of the present application is obtained by gravimetric testing, and the specific operation steps are carried out in accordance with GB / T 13025.8-91 General experimental method for salt industry - determination of sulfate ions.

[0050] In an optional embodiment, the porosity of the positive electrode active material precursor is 15-30%. If the porosity of the positive electrode active material precursor is too large, it will affect the cycle performance of the battery, and if it is too small, it will affect the gram capacity of the battery. By controlling the porosity of the positive electrode active material precursor within the above range, especially within the preferred range, the cycle performance of the battery can be improved while ensuring a higher gram capacity. For example, the porosity of the positive electrode active material precursor is 15%, 20%, 25%, 30% or within the range formed by any two of the above values.

[0051] In a third aspect, the present application provides a method for preparing a positive electrode active material, which is prepared by mixing the positive electrode active material precursor with a lithium source and then sintering the mixture.

[0052] In an optional embodiment, the sintering includes a first sintering and a second sintering.

[0053] In an optional embodiment, the sintering temperature of the first sintering is 450°C to 600°C, and the holding time is 4h to 6h. For example, the sintering temperature of the first sintering is 450°C, 500°C, 550°C, 600°C, or within the range of any two of the above values, and the holding time is 4h, 5h, 6h, or within the range of any two of the above values.

[0054] In an optional embodiment, the sintering temperature of the second sintering is 750°C to 900°C, and the holding time is 12h to 20h. For example, the sintering temperature of the second sintering is 750°C, 800°C, 900°C, or within the range of any two of the above values, and the holding time is 12h, 16h, 20h, or within the range of any two of the above values.

[0055] In an optional embodiment, the mass ratio of the positive electrode active material precursor to the lithium source is 1000:400-500.

[0056] In an optional embodiment, the sintering atmosphere is compressed air, and the compressed air is replenished at a rate of 30L to 40L / min per cubic meter of space.

[0057] In an optional embodiment, the lithium source includes one or more of lithium carbonate, lithium hydroxide, and lithium oxide.

[0058] In an optional embodiment, the preparation method of the positive electrode active material precursor includes using salt solution 2 as the base liquid, adding salt solution 1 and alkali solution to react, separating the solid and the liquid, taking the solid, drying it, and sieving it to obtain the positive electrode active material precursor; the preparation methods of the salt solution 1 and the salt solution 2 both include the following steps: mixing a nickel source, a cobalt source, and a manganese source with water to obtain; the preparation method of the alkali solution includes the following steps: mixing sodium carbonate and a complexing agent with water to obtain. The applicant has found that using salt solution 2 as the base liquid can provide a relatively stable reaction starting environment, which is convenient for forming a stable precursor synthesis process, and can prevent local salt / alkali excess caused by instantaneous system concentration changes at the start of the reaction. This phenomenon will cause the particles to agglomerate, the sphericity will deteriorate, the particle size will increase, and the compaction will decrease. However, when salt solution 2 and alkali solution are both base liquids, precipitation will be directly produced. Using alkali solution alone as the base liquid will result in uneven growth and excessive particle size.

[0059] In an optional embodiment, the nickel source is nickel sulfate hexahydrate, the cobalt source is cobalt sulfate heptahydrate, the manganese source is manganese sulfate monohydrate, and the complexing agent is one or more of ammonia water, ammonium oxalate, and ammonium citrate.

[0060] In an optional embodiment, the concentration of the complexing agent in the prepared alkali solution is 10 g / L to 20 g / L. For example, the concentration of the complexing agent is 10 g / L, 15 g / L, 20 g / L, or within the range of any two of the above values.

[0061] In an optional embodiment, the concentration of the salt solution 1 is 1-2 mol / L. For example, the concentration of the salt solution 1 is 1 mol / L, 1.5 mol / L, 2 mol / L, or within a range formed by any two of the above values.

[0062] In an optional embodiment, the concentration of the salt solution 2 is 0.01-0.5 mol / L. The applicant has found that by limiting the concentration of the base solution within this range, a precursor with small particle size and uniform particle size distribution can be obtained. For example, the concentration of the salt solution 2 is 0.01 mol / L, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L or within the range formed by any two of the above values.

[0063] In an optional embodiment, the concentration of the alkali solution is 0.01-0.5 mol / L. For example, the concentration of the alkali solution is 0.01 mol / L, 0.1 mol / L, 0.3 mol / L, 0.5 mol / L, or within the range of any two of the above values.

[0064] In an optional embodiment, the volume of the bottom liquid is 10%-20% of the volume of the reactor. The applicant has found that by limiting the volume of the bottom liquid to this range, a small-sized precursor can be obtained. If more bottom liquid is used, the precursor particle size is larger, and less bottom liquid is not conducive to obtaining a uniform precursor. For example, the bottom liquid is 10%, 15%, 20% of the volume of the reactor, or within the range of any two of the above values.

[0065] In an optional embodiment, the reaction temperature is between 30° C. and 60° C. For example, the reaction temperature is 30° C., 45° C., 60° C., or a range formed by any two of the above values.

[0066] In some embodiments, the pH value of the reaction system is between 7.0 and 8.5. For example, the pH value of the reaction system is 7.0, 8.0, 8.5, or within a range formed by any two of the above values.

[0067] In some embodiments, the drying temperature is 80° C. to 150° C. For example, the drying temperature is 80° C., 100° C., 150° C., or a range formed by any two of the above values.

[0068] In some embodiments, the drying time is 12 hours to 36 hours. For example, the drying time is 12 hours, 20 hours, 36 hours, or a range formed by any two of the above values.

[0069] In some embodiments, the dripping speed of the saline solution 1 is 400-1200 ml / h.

[0070] In some embodiments, the dropping speed of the alkaline solution 1 is controlled so as to control the pH range of the reaction system.

[0071] In a fourth aspect, the present application provides a positive electrode sheet, which is made from any of the positive electrode active materials described above or the positive electrode active material prepared by the preparation method described above.

[0072] In a fifth aspect, the present application provides a lithium-ion secondary battery, comprising the positive electrode sheet described in the fourth aspect of the present application, and also comprising a separator, a negative electrode sheet and an electrolyte.

[0073] In an optional embodiment, the electrolyte includes a non-aqueous organic solvent, a conductive lithium salt, and an additive. Preferably, the non-aqueous organic solvent includes at least one of cyclic carbonates, and at least one of linear carbonates and linear carboxylates. Preferably, the conductive lithium salt includes lithium hexafluorophosphate, bisfluorosulfonyl imide lithium salt, bistrifluoromethylsulfonyl imide lithium, difluorophosphate, lithium tetrafluoroborate, lithium hexafluoroantimonate, lithium hexafluoroarsenate, difluorooxalate borate lithium, tetrafluorooxalate phosphate lithium, difluorobisoxalate phosphate lithium, bisoxalate borate lithium, 4,5-dicyano-2-trifluoromethyl-imidazole lithium, bis(trifluoromethylsulfonyl)imide lithium, bis(pentafluoroethylsulfonyl)imide lithium, tris(trifluoromethylsulfonyl)methyl lithium and bis(trifluoromethylsulfonyl)imide lithium. Preferably, the additive includes one or more of nitrile compounds, vinylene carbonate and 1,3-propylene sultone.

[0074] Preferably, the cyclic carbonate includes one or more of ethylene carbonate, propylene carbonate, butylene carbonate, and fluoroethylene carbonate; the linear carbonate includes one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, and methyl propyl carbonate; the linear carboxylic acid ester includes one or more of ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, and ethyl butyrate.

[0075] In an optional embodiment, the negative electrode sheet is selected from a lithium sheet or includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material. In some embodiments, the negative electrode active material may adopt a negative electrode active material for a battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, hard carbon, silicon-based materials, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon-oxygen compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys.

[0076] In an optional embodiment, the separator may be a separator material for batteries known in the art. For example, the separator includes a polypropylene separator coated with a ceramic layer on one or both sides of a polypropylene substrate. The ceramic material in the ceramic layer includes, but is not limited to, one or more of CeO2, MgAl2O4, ZrO, and TiO2.

[0077] The electrolyte used in the lithium ion secondary battery of the present application may include any technology disclosed in the prior art.

[0078] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0079] Example 1

[0080] The preparation method of the positive electrode active material provided in this embodiment is as follows: nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate are weighed according to the molar ratio of nickel, cobalt and manganese elements Ni:Co:Mn=30:10:60, and then water is added to dissolve them at a total molar concentration of Ni, Co and Mn of 2 mol / L to form a salt solution 1. At the same time, nickel sulfate hexahydrate, cobalt sulfate heptahydrate and manganese sulfate monohydrate are weighed according to the molar ratio of nickel, cobalt and manganese elements Ni:Co:Mn=30:10:60, and water is added to dissolve them to prepare 12L of salt solution 2 with a total molar concentration of Ni, Co and Mn of 0.3 mol / L. Sodium carbonate is added to water and dissolved at a concentration of 2 mol / L to prepare an alkali solution 1.

[0081] Add 12L of salt solution 2 into a 50L reactor as the base liquid, adjust the reactor body temperature to 55°C, and the reactor stirring speed to 1300rpm. Add salt 1 and alkali solution 1 into the reactor respectively through a peristaltic pump. The dripping speed of salt 1 is 1100ml / h. The dripping speed of alkali solution 1 is controlled to maintain the pH of the system at 7.5±0.02. React for 20h. After reaching the target particle size, stop the reaction, maintain the reactor body temperature at 55°C, reduce the stirring speed to 400rpm, and age at this temperature and speed for 24h. After aging, wash and filter, and dry in a 130°C blast oven for 24h. Pass through a 400-mesh sieve to obtain a lithium-rich material precursor; wherein, the cleaning process of this embodiment is as follows: water-to-material ratio (mass ratio) 10:1, wash for 3h each time, and repeat the cleaning 7 times. The slice scanning results of the positive electrode active material precursor obtained in Example 1 are shown in Figure 4 shown.

[0082] The obtained lithium-rich material precursor and battery-grade lithium carbonate are mixed in a mass ratio of precursor: lithium carbonate = 1:0.45. After mixing evenly, they are sintered in a pot. The sintering temperature curve is divided into two platforms. The middle platform uses 550°C and lasts for 6 hours for sintering. The high-temperature platform uses 800°C and lasts for 16 hours for sintering. After sintering, the materials are dried and packaged and stored in a dry environment.

[0083] The lithium ion secondary battery provided in this embodiment is prepared by the following method:

[0084] Step 1: Prepare the positive electrode

[0085] The positive electrode active material, the conductive agent acetylene black, and the binder polyvinylidene fluoride PVDF are fully stirred and mixed in an N-methylpyrrolidone solvent system in a mass ratio of 90:5:5, and then coated on an aluminum foil for drying, and then cold pressed and cut into corresponding positive electrode sheets.

[0086] Step 2: Battery Preparation

[0087] A mixed solution consisting of lithium hexafluorophosphate, organic solvent ethylene carbonate (EC) and additive vinyl carbonate (VC) was used as the electrolyte, and the weight ratio of lithium salt: organic solvent: additive was 12:83:5. A 0.4 mm thick lithium sheet was used as the negative electrode sheet, and the negative electrode sheet, positive electrode sheet and separator (using 18 μm polyethylene as the base separator, one side coated with 7 μm polytetrafluoroethylene, and the other side coated with 7 μm alumina ceramic) prepared in Example 1 were assembled into a winding core, placed in a shell, and the required battery was obtained after baking and injection steps.

[0088] Example 2

[0089] The preparation process is basically the same as that in Example 1, except that the total molar concentration of Ni, Co, and Mn in the salt solution 2 is different, which is 0.2 mol / L in this example, resulting in different physical parameters of the positive electrode active material precursor and the positive electrode active material, as shown in Tables 1 and 2 for details.

[0090] Example 3

[0091] The preparation process is basically the same as that in Example 1, except that the total molar concentration of Ni, Co, and Mn in the salt solution 2 is different, which is 0.1 mol / L in this example, resulting in different physical parameters of the positive electrode active material precursor and the positive electrode active material, as shown in Tables 1 and 2 for details.

[0092] Example 4

[0093] The preparation process is basically the same as that in Example 1, except that the total molar concentration of Ni, Co, and Mn in the salt solution 2 is different, which is 0.05 mol / L in this example, resulting in different physical parameters of the positive electrode active material precursor and the positive electrode active material, as shown in Tables 1 and 2 for details.

[0094] Example 5

[0095] The preparation process is basically the same as that in Example 1, except that the volume of the base liquid and the reaction time are different. In this embodiment, 8 L of salt solution 2 is added to a 50 L reactor as the base liquid, and the reaction time is extended to 30 h, resulting in different porosity of the positive electrode active material precursor, porosity and specific surface area of ​​the positive electrode active material, as shown in Tables 1 and 2 for details.

[0096] Example 6

[0097] The preparation process is basically the same as that in Example 1, except that the volume of the base liquid is different. In this embodiment, 25 L of salt solution 2 is added to a 50 L reactor as the base liquid, resulting in different porosity of the positive electrode active material precursor, porosity and specific surface area of ​​the positive electrode active material, as shown in Tables 1 and 2 for details.

[0098] Example 7

[0099] The preparation process is basically the same as that in Example 1, except that the stirring speed during the reaction process is different. In this example, the stirring speed is reduced from 1300 rpm to 1000 rpm, resulting in different particle size parameters of the positive electrode active material precursor and the positive electrode active material, as shown in Tables 1 and 2 for details.

[0100] Example 8

[0101] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 6 times and the aging time is 22 hours, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, as shown in Table 3 for details.

[0102] Example 9

[0103] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 5 times and the aging time is 20 hours, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, as shown in Table 3 for details.

[0104] Example 10

[0105] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 4 times and the aging time is 18 hours, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, see Table 3 for details.

[0106] Embodiment 11

[0107] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 3 times and the aging time is 16 hours, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, see Table 3 for details.

[0108] Example 12

[0109] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 2 times and the aging time is 14 hours, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, see Table 3 for details.

[0110] Example 13

[0111] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 1 and the aging time is 12 h, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, as shown in Table 3 for details.

[0112] Embodiment 14

[0113] The preparation process is basically the same as that in Example 1, except that in this embodiment, the molar ratio of nickel, cobalt and manganese in salt solution 1 and salt solution 2 is Ni:Co:Mn=20:20:60, and the chemical formula is Li 1.3 Ni 0.2 Co 0.2 Mn 0.6 O2 positive electrode active material.

[0114] Embodiment 15

[0115] The preparation process is basically the same as that in Example 1, except that in this example, the molar ratio of nickel, cobalt and manganese in salt solution 1 and salt solution 2 is Ni:Co:Mn=44:2:54, and the chemical formula is Li 1.3 Ni 0.42 Co 0.02 Mn 0.54 O2 positive electrode active material.

[0116] Example 16

[0117] The preparation process is basically the same as that in Example 1, except that in this embodiment, the lithium-rich material precursor and battery-grade lithium carbonate are mixed according to the mass ratio of precursor: lithium carbonate = 1:0.82 to obtain a chemical formula of Li 1.6 Ni 0.3 Co 0.1 Mn 0.6 O2 positive electrode active material.

[0118] Embodiment 17

[0119] The preparation process is basically the same as that in Example 1, except that in this embodiment, the lithium-rich material precursor and battery-grade lithium carbonate are mixed according to the mass ratio of precursor: lithium carbonate = 1:0.613 to obtain a chemical formula of Li 1.22 Ni 0.3 Co 0.1 Mn 0.6 O2 positive electrode active material.

[0120] Comparative Example 1

[0121] The preparation process is basically the same as that of Example 1, except that the base solution is different. In this example, "adding 0.03 mol / L oxalic acid to 12 L of deionized water to make the pH value of the solution 4.5 to obtain a weakly acidic solution" is used instead of "adding 12 L of salt solution 2", resulting in different physical parameters of the positive electrode active material precursor and the positive electrode active material, as shown in Tables 1 and 2. The slice scanning results of the positive electrode active material precursor prepared in Comparative Example 1 are shown in Figure 3 shown.

[0122] Comparative Example 2

[0123] The preparation process is basically the same as that in Example 1, except that the base solution is different. In this embodiment, "adding 0.03 mol / L ammonia water to 12 L of deionized water to make the pH value of the solution 7.5 to obtain a weakly alkaline solution" is used instead of "adding 12 L of salt solution 2", resulting in different physical parameters of the positive electrode active material precursor and the positive electrode active material, see Tables 1 and 2 for details.

[0124] Comparative Example 3

[0125] The preparation process is basically the same as that in Example 1, except that the base liquid is different. In this embodiment, "12 L of alkaline solution 2" is used instead of "12 L of salt solution 2", wherein the preparation method of alkaline solution 2 is as follows: sodium carbonate is dissolved in water at a concentration of 0.3 mol / L to prepare alkaline solution 1, resulting in different physical parameters of the positive electrode active material precursor and the positive electrode active material, see Tables 1 and 2 for details.

[0126] Comparative Example 4

[0127] The preparation process is basically the same as that in Example 1, except that the aging time and the number of cleaning times are different. In this embodiment, the number of cleaning times is 0 and the aging time is 6 h, resulting in different sulfate content and sphericity of the positive electrode active material precursor and different sphericity and specific surface area of ​​the positive electrode active material, as shown in Table 3 for details.

[0128] Comparative Example 5

[0129] The preparation process is basically the same as that in Example 1, except that the reaction time and the aging time are different. In this example, the reaction time is shortened to 12 h and the aging time is shortened to 10 h, resulting in different particle size parameters of the positive electrode active material precursor and the positive electrode active material, as shown in Tables 1 and 2 for details.

[0130] Comparative Example 6

[0131] The preparation process is basically the same as that in Example 1, except that the reaction time and the aging time are different. In this example, the reaction time is extended to 48 h, and the aging time is extended to 48 h, resulting in different particle size parameters of the positive electrode active material precursor and the positive electrode active material, see Tables 1 and 2 for details.

[0132] Table 1 Physical parameters of positive electrode active material precursors

[0133]

[0134] Table 2 Physical parameters of positive electrode active materials

[0135]

[0136]

[0137] Table 3 Physical parameters of positive electrode active material precursor and positive electrode active material

[0138]

[0139] Test Case

[0140] (1) The positive electrode active materials obtained in each embodiment and comparative example were subjected to powder tap density test, compaction density and XRD test, respectively. I1 is the peak intensity of the first diffraction peak at 2θ=17-19° in the XRD spectrum; I2 is the peak intensity of the second diffraction peak at 2θ=43-46° in the XRD spectrum; I3 is the peak intensity of the superlattice peak at 20-25°; the results are shown in Tables 2 and Figure 5 ;

[0141] (2) Test the first cycle charge and discharge capacity of the battery obtained in each embodiment and comparative example under a voltage system of 2 to 4.6V, and the subsequent discharge capacity under a voltage system of 2 to 4.8V; specifically: after the battery is manufactured, let it stand for 12 hours; after standing, put the battery on the blue power test system; charge to 4.6V with 0.1C and then switch to constant voltage charging until the current is less than or equal to 0.02C; let it stand for 10 minutes; discharge to 2V with 0.1C; record the charge and discharge data; record the charge and discharge capacity, and calculate the first effect. Charge to 4.8V with 0.1C and then switch to constant voltage charging until the current is less than or equal to 0.02C; let it stand for 10 minutes; discharge to 2V with 0.1C; record the charge and discharge capacity, and calculate the first effect.

[0142] The cycle performance of the batteries obtained in the embodiments and comparative examples under the 2-4.6V 0.5C voltage system was tested; specifically, after the first cycle and 4.8V charge and discharge were tested; charging to 4.6V at 0.5C and then switching to constant voltage charging until the current was less than or equal to 0.02C; leaving for 10 minutes; discharging to 2V at 0.5C; cycling 100 times; recording the charge and discharge data; and calculating the capacity retention rate.

[0143] The test results of the above items are shown in Table 4.

[0144] Table 4 Test results of lithium-ion secondary batteries

[0145]

[0146]

[0147] Compared with Comparative Examples 1-A5, the tap density of the positive electrode active material prepared in each embodiment of the present invention is significantly improved, the processing performance is improved, and the compaction density is also significantly improved. At the same time, the lithium ion battery composed of the positive electrode active material has a high discharge specific capacity, and the 2-4.8V discharge specific capacity is greater than 275mAh / g. In addition, the lithium ion batteries of each embodiment of the present invention have good performance in long-cycle applications (see Figure 1 and Figure 2 ).

[0148] Compared with Comparative Examples A5 and A6, the particle size parameters of the positive electrode active materials or positive electrode active material precursors prepared in the embodiments of the present invention are within a suitable range, so that the lithium-ion battery has higher cycle stability and discharge specific capacity.

[0149] For Example A4, the positive electrode active materials prepared in various embodiments of the present invention have higher sphericity, so that the lithium-ion battery has higher cycle stability and discharge specific capacity.

[0150] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection created by this application.

Claims

1. A positive electrode active material, characterized in that: The chemical formula of the positive electrode active material is as follows: Li 1+q Ni x Co y Mn z O2, and 0<q≤1, 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material is 55-150nm, the secondary particle size Dv50 is 3μm-5μm, Dv10 is 1μm-2μm, Dv90 is 7μm-9μm, (Dv90-Dv10) / Dv50 is 1.3-1.8, and the sphericity is 0.45-0.90; preferably 0.6-0.

90.

2. The positive electrode active material according to claim 1, characterized in that The specific surface area of ​​the positive electrode active material is 1.0-4.0 m 2 / g, preferably 1.5-2.5m 2 / g.

3. The positive electrode active material according to claim 1 or 2, characterized in that: The porosity of the positive electrode active material is 1-15%, preferably 3-8%.

4. The positive electrode active material according to claim 1 or 2, characterized in that: The sulfate content in the positive electrode active material is 66-200 ppm, preferably 66-90 ppm.

5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The positive electrode active material satisfies one or two of the following AB: A. Powder X-ray diffraction expressed in 2θ angles, with a superlattice peak at 20-25°; optionally, the peak intensity of the superlattice peak at 2θ of 20-25° is 500-1000; B. The XRD spectrum of the positive electrode active material satisfies the following relationship: 1.1≤I1 / I2≤1.5; wherein I1 is the peak intensity of the first diffraction peak at 2θ=17-19° in the XRD spectrum; I2 is the peak intensity of the second diffraction peak at 2θ=43-46° in the XRD spectrum.

6. A positive electrode active material precursor, characterized in that: The chemical formula of the positive electrode active material precursor is as follows: Ni x Co y Mn z (OH)2, and 0.2≤x≤0.45, 0.02≤y≤0.20, 0.35≤z≤0.78; the primary particle size of the positive electrode active material precursor is 20-65nm, the secondary particle size Dv50 is 3μm-5μm, Dv10 is 1μm-2μm, Dv90 is 7μm-9μm, (Dv90-Dv10) / Dv50 is 1.3-1.8, and the sphericity is 0.4-0.85; preferably 0.6-0.

85.

7. The positive electrode active material precursor according to claim 6, characterized in that: The sulfate content of the positive electrode active material precursor is 60-180 ppm, preferably 60-80 ppm.

8. The positive electrode active material precursor according to claim 6 or 7, characterized in that: The porosity of the positive electrode active material precursor is 15-30%, preferably 19-23%.

9. A positive electrode sheet, characterized in that: The positive electrode active material comprises any one of claims 1 to 5.

10. A lithium ion secondary battery, characterized in that: The invention comprises the positive electrode sheet as claimed in claim 9, and also comprises a separator, a negative electrode sheet and an electrolyte.